PENDAMPINGAN PENYUSUNAN MODUL AJAR PADA KURIKULUM MERDEKA MENUJU SEKOLAH MENENGAH KEJURUAN PUSAT KEUNGGULAN - Yusro, Muhammad; Yuliatmojo, Pitoyo; Triwardana, Deni; Wiyantoro, Hadi; Sulistiyo, Catur; Ismaninggar; Haryanto, Mudji (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2023)
Abstract The Center for Excellence Vocational High School Program (SMK-PK) is a vocational school development program with special skill competencies to improve quality and performance. This program is strengthened by partnerships and alignment with the business world, industrial world and the world of work which ultimately becomes a reference vocational school and driving school. To prepare SMK to become SMK-PK, mentoring activities are needed to provide knowledge and skills about the SMK-PK concept, independent vocational school curriculum and vocational school learning tools. This activity aims to assist teachers in compiling teaching modules in an independent curriculum for superior central vocational high schools (SMK-PK). Participants are given material related to learning outcomes, learning objectives, flow of learning objectives, and teaching modules in the independent curriculum. There were 34 participants in this activity consisting of teachers from SMKN 5 Jakarta, and teacher representatives from SMKS PGRI 8, SMKS Satya Bakti 1, and SMKS Budi Murni 1. The results of the activity evaluation obtained from filling in the online questionnaire showed that all participants (100 %) stated that they had received enlightenment about SMK-PK, the majority (97.1%) had a better understanding of the preparation of teaching modules, the material presented was very clear and easy to understand, the material provided supported performance improvement and was useful according to needs. In the next activity, assistance needs to be provided in the form of a clinic for preparing teaching modules in the independent curriculum. Abstrak Program Sekolah Menengah Kejuruan Pusat Keunggulan (SMK-PK) merupakan program pengembangan SMK dengan kompetensi keahlian tertentu dalam rangka peningkatan kualitas dan kinerja. Program ini diperkuat dengan kemitraan dan penyelarasan dengan dunia usaha, dunia industri, dunia kerja, yang akhirnya menjadi SMK rujukan sekaligus sekolah penggerak. Untuk mempersiapkan SMK menjadi SMK-PK diperlukan kegiatan pendampingan yang bertujuan memberikan pengetahuan dan keterampilan tentang konsep SMK-PK, kurikulum merdeka jenjang SMK serta perangkat pembelajaran SMK. Kegiatan ini bertujuan untuk mendampingi guru menyusun modul ajar pada kurikulum merdeka menuju sekolah menengah kejuruan pusat keunggulan (SMK-PK). Peserta diberikan materi terkait capaian pembelajaran, tujuan pembelajaran, alur tujuan pembelajaran dan modul ajar pada kurikulum merdeka. Peserta kegiatan ini berjumlah 34 orang yang terdiri dari para guru SMKN 5 Jakarta, dan perwakilan guru dari SMKS PGRI 8, SMKS Satya Bakti 1 dan SMKS Budi Murni 1. Hasil evaluasi kegiatan yang diperoleh dari isian kuesioner online menunjukkan bahwa semua peserta (100%) menyatakan telah mendapatkan pencerahan tentang SMK-PK, mayoritas (97,1%) menjadi lebih paham tentang penyusunan modul ajar, materi yang disajikan sangat jelas dan mudah dipahami, materi yang diberikan mendukung peningkatan kinerja serta bermanfaat sesuai kebutuhan. Pada kegiatan selanjutnya perlu dilakukan pendampingan berupa klinik penyusunan modul ajar pada kurikulum merdeka.